Status of periodontal tissue in women accessing oral contraceptives - Borysenko, A.; Vatankha, T. (Actual Dentistry, 2018)
Summary. In the pathogenesis of periodontal diseases of women, an imbalance of sex hormones is important. It is considered as one of the provocative factors of periodontal disease. According to the literature, oral contraceptives may cause changes in periodontium similar to changes in puberty and pregnancy. Objective: to determine the characteristics of the periodontal disease of women taking oral hormonal contraceptives for the purpose of planning pregnancy. Material and methods. A survey was conducted on 110 women, the main group was 80 women taking oral contraceptives, control 30 women who did not take them. To quantify the state of periodontal tissues, the Schiller-Pisarev test [2], the Green-Vermillion Hygiene Index [3,4], the Gingival Index (GI) by H. Loe, J. Silness [9], the Bleeding Index by H.R.Muhlemann [7], the index PMA by S. Parma [8], the index of the dental plaque of interdental gaps (API) by Lange [6] Results. The investigation showed that inflammatory and degenerative-inflammatory diseases of the periodontal tissue were detected in 78 (97.5%) women in the primary and in 28 (93.3%) women in the control group. They found an unsatisfactory state of oral hygiene in both groups. In 70 (89.7%) women in the primary group and 23 (82.1%) controls, chronic catarrhal gingivitis was detected; Generalized periodontitis was detected in 8 (11.3%) women in the primary group and in 3 (10.0%) women in the control group. Conclusions. Analysis of the data shows a significant level of inflammatory and dystrophic-inflammatory periodontal disease in the examined women. Attention is drawn to a somewhat greater extent of their prevalence in women taking contraceptives. Key words: periodontal disease, oral contraceptives.